Targeting miRNA-based medicines to cystic fibrosis airway epithelial cells using nanotechnology - McKiernan, Paul J (Dove Medical Press, 2013)
Cystic fibrosis (CF) is an inherited disorder characterized by chronic airway inflammation. microRNAs (miRNAs) are endogenous small RNAs which act on messenger (m) RNA at a post transcriptional level, and there is a growing understanding that altered expression of miRNA is involved in the CF phenotype. Modulation of miRNA by replacement using miRNA mimics (premiRs) presents a new therapeutic paradigm for CF, but effective and safe methods of delivery to the CF epithelium are limiting clinical translation. Herein, polymeric nanoparticles are investigated for delivery of miRNA mimics into CF airway epithelial cells, using miR-126 as a proof-of-concept premiR cargo to determine efficiency. Two polymers, polyethyleneimine (PEI) and chitosan, were used to prepare miRNA nanomedicines, characterized for their size, surface (zeta) potential, and RNA complexation efficiency, and screened for delivery and cytotoxicity in CFBE41o- (human F508del cystic fibrosis transmembrane conductance regulator bronchial epithelial) cells using a novel high content analysis method. RNA extraction was carried out 24 hours post transfection, and miR-126 and TOM1 (target of Myb1) expression (a validated miR-126 target) was assessed. Manufacture was optimized to produce small nanoparticles that effectively complexed miRNA. Using high content analysis, PEI-based nanoparticles were more effective than chitosan-based nanoparticles in facilitating uptake of miRNA into CFBE41o- cells and this was confirmed in miR-126 assays. PEI-premiR-126 nanoparticles at low nitrogen/phosphate (N/P) ratios resulted in significant knockdown of TOM1 in CFBE41o- cells, with the most significant reduction of 66% in TOM1 expression elicited at an N/P ratio of 1:1 while chitosan-based miR-126 nanomedicines failed to facilitate statistically significant knockdown of TOM1 and both nanoparticles appeared relatively nontoxic. miRNA nanomedicine uptake can be qualitatively and quantitatively assessed rapidly by high content analysis and is highly polymer-dependent but, interestingly, there is not a direct correlation between the levels of miRNA uptake and the downstream gene knockdown. Polymeric nanoparticles can deliver premiRs effectively to CFBEs in order to modulate gene expression but must be tailored specifically for miRNA delivery.